Nitrogen supply and rainfall affect ammonia emissions from dairy cattle excreta and urea applied on warm‐climate pastures. Issue 6 (30th November 2020) - Longhini, Vanessa Zirondi; Cardoso, Abmael da Silva; Berça, Andressa Scholz; Boddey, Robert Michael; Reis, Ricardo Andrade; Dubeux Junior, José Carlos Batista; Ruggieri, Ana Cláudia
Abstract: Cattle excreta and nitrogen (N) fertilizer deposited on tropical grasslands are important sources of ammonia (NH3 ) emission. We conducted three field trials (wet, intermediate, and dry conditions) to quantify NH3 emissions from urea fertilizer and simulated excretions of heifer urine and dung on warm‐climate grasslands in Brazil. Heifer excreta were derived from pastures of palisadegrass [ Urochloa brizantha (Hochst. ex A. Rich.) R. D. Webster 'Marandu'] under three forms of N supply (without or with N fertilization [0 or 150 kg N ha −1  yr −1 ] or mixed with forage peanut [ Arachis pintoi 'Amarillo']). Cumulative NH3 –N emissions across rainfall conditions were 7.6–16.6% (mean, 11.7%) for urine, 1.4–2.9% (mean, 2.0%) for dung, and 11.2–20.5% (mean, 14.8%) for urea. Ammonia loss from urine was significantly greater than from dung under all rainfall conditions. Emission from urine and dung differed from those when urea was applied on palisadegrass. There were greater NH3 emissions from urine in the wetter times of the year. Heifer excreta from N‐fertilized pasture had greater NH3 emission than excreta from the grass–legume mixture and unfertilized palisadegrass. Urea applied on palisadegrass presented greater NH3 emissions in wet rainfall conditions compared with dry conditions but did not differ from intermediate conditions. Our study showed that N‐fertilized systems increase N losses as NH3 emission from excreta, and emissions from urea fertilizer must be included in this system. Heifer excreta and urea fertilizer deposited on warm‐climate grasslands increased the NH3 emissions mainly under wet conditions.